Postmortem genetic diagnosis of hereditary leiomyomatosis and renal cell carcinoma syndrome: Identification through normal kidney tissues after surgical removal - Shodai Suzuki; Yoshiyuki Yamamoto; Taigo Kato; Koji Hatano; Takahiro Matsui; Kae Hashimoto; Takako Miyamura; Yoji Nagashima; Norio Nonomura; Atsunari Kawashima (IJU Case Reports)
Introduction Hereditary leiomyomatosis and renal cell cancer is an autosomal dominant disorder caused by germline mutations in the FH gene and is associated with poor prognosis of aggressive renal cancer. Case presentation A 33‐year‐old man presented with asymptomatic gross hematuria and was diagnosed with a right renal tumor, cT3aN1M0. He underwent open radical nephrectomy, and pathological examination revealed papillary renal cell carcinoma. Despite aggressive treatment, the disease progressed rapidly, and discussions regarding genetic testing could not take place during his lifetime, although circulating‐tumor DNA showed mutation of FH gene. After death, his wife requested postmortem genetic testing. Genetic analysis using DNA extracted from normal kidney tissues in surgical specimens (blood sample absence) confirmed the FH mutation, and hereditary leiomyomatosis and renal cell cancer was diagnosed posthumously. Conclusion This highlights the utility of postmortem genetic testing of surgical specimens to diagnose hereditary leiomyomatosis and renal cell cancer and provide genetic counseling to families, despite limitations during the patient's life.